ANALISIS KOMUNIKASI DATA PADA LESAN TEMBAK UNTUK LATIHAN TEKNIK TEMPUR CEPAT BERBASIS LORA 1278 - IPutu Eka Yulianto (MULTITEK INDONESIA, 2019)
To assist the soldier in training the agility and accuracy required of technology for movement and targets, factors that need to be considered like, field conditions, target movement and personnel movement against the technology used, an understanding of firing theory and the physical and psychological condition of the personnel themselves. To realize the application the authors use the communication to move the shot will be tested using long-range radio nRF24l01 which serves to send and receive data between sensors with firing shots. By analyzing data communications that have set points and using TDM (Time Division Multiplexing) in PDM (Pulse Duration Modulation) method, it will get the result of tool testing.